GLOBALIZATION AND MIGRATION FROM THE PERSPECTIVE OF ETHNOSYMBOLIST AND CIVIC NATIONALISM - Yaman, Haluk; Kartal, Meryem (My University, 2023)
Nationalist ideology, which emerged in the 18th century and profoundly influenced the 19th, occupies a significant position in human affairs and the concept of the nation-state, despite its contradictions and multidimensional structure. As nationalism gained traction in the ethnosymbolist mentality through values such as race, religion, language, and ethnicity, it acquired different meanings around the concept of civic nationalism in the aftermath of modernization and globalization. The specific conditions of societies were affected by globalization and migration, leading to the differentiation of the nationalist mindset between ethnic nationalism and civic nationalism. Beginning in the 1980s, Western civic nationalism was described as \"good nationalism,\" while Eastern nationalism, informed by ethnosymbolism, was \"bad nationalism.\" This study seeks the answer to the question of how the stances of ethnosymbolism and civic nationalism towards globalization and migration were shaped. In this context, the study examines the convergence between ethnosymbolist nationalism and civic nationalism, as well as the factors that led to it, from a historical and holistic perspective and by using a comparative method.
Keywords: Globalization; Migration; Civic Nationalism; Ethnosymbolist Nationalism; Nationalism.